A new approach of probe sonication assisted ionic liquid conversion of glucose, cellulose and biomass into 5-hydroxymethylfurfural - Sarwono, A. (Elsevier B.V., 2017)
5-Hydroxymethylfurfural (HMF) has been identified as a promising biomass-derived platform chemical. In this study, one pot production of HMF was studied in ionic liquid (IL) under probe sonication technique. Compared with the conventional heating technique, the use of probe ultrasonic irradiation reduced the reaction time from hours to minutes. Glucose, cellulose and local bamboo, treated with ultrasonic, produced HMF in the yields of 43, 31 and 13 respectively, within less than 10 min. The influence of various parameters such as acoustic power, reaction time, catalysts and glucose loading were studied. About 40 HMF yield at glucose conversion above 90 could be obtained with 2 of catalyst in 3 min. Negligible amount of soluble by-product was detected, and humin formation could be controlled by adjusting the different process parameters. Upon extraction of HMF, the mixture of ionic liquid and catalyst could be reused and exhibited no significant reduction of HMF yield over five successive runs. The purity of regenerated C4C1imCl and HMF was confirmed by NMR spectroscopy, indicating neither changes in the chemical structure nor presence of any major contaminants during the conversion under ultrasonic treatment. 13C NMR suggests that C4C1imCl/CrCl3 catalyses mutarotation of α-glucopyranose to β-glucopyranose leading to isomerization and finally conversion to HMF. The experimental results demonstrate that the use of probe sonication technique for conversion to HMF provides a positive process benefit. © 2017 Elsevier B.V.